Adsorption of Rhodamine 6G Dye onto Al-MCM-41 and MCM-41 Mesoporous Materials - Houda Douba; Ourida Mohammedi; Benamar Cheknane (Kemija u Industriji, 2022)
The present study aimed to evaluate the potential of mesoporous silica MCM-41 and Al-MCM-41 (molar ratio Si/Al = 20) for the removal of Rhodamine 6G (Rh6G) from aqueous solution. The adsorbents were characterised by XRD, FTIR, SEM-EDX, BET, and UV-Raman. Obtained results related to XRD analysis indicated that the MCM-41 structure remained intact after the incorporation of Al species. Kinetic adsorption study showed that the higher removal (88.75 %, 26.62 mg g−1) of Rh6G dye was achieved by Al-MCM-41 at 60 min. FTIR analysis showed that hydrogen bonding played the dominant role in the Rh6G removal mechanism, while the pH results showed that electrostatic interaction was also a key factor. This study shows that the prepared mesoporous materials are inexpensive and efficient adsorbents for the removal of cationic dyes.